2010
DOI: 10.1016/j.molcel.2010.06.019
|View full text |Cite
|
Sign up to set email alerts
|

DNA Damage Signaling Recruits the Rtt107-Slx4 Scaffolds via Dpb11 to Mediate Replication Stress Response

Abstract: The DNA damage checkpoint kinase Mec1(ATR) is critical for maintaining the integrity of replication forks. Though it has been proposed to promote fork repair, the mechanisms by which Mec1 regulates DNA repair factors remain unclear. Here, we found that Mec1 mediates a key interaction between the fork protein Dpb11 and the DNA repair scaffolds Slx4-Rtt107 to regulate replication stress response. Dissection of the molecular basis of the interaction reveals that Slx4 and Rtt107 jointly bind Dpb11 and that Slx4 ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
137
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(155 citation statements)
references
References 26 publications
14
137
0
Order By: Relevance
“…5B). SMC5/6 is known to be recruited to DSBs by Rtt107 when phosphorylated by the DNA damage checkpoint kinase Mec1 (De Piccoli et al 2006;Ohouo et al 2010;Leung et al 2011;Ullal et al 2011). Consistently, the rtt107Δ strain also compromised relocation of DSBs to the NE in both stages of the cell cycle (Fig.…”
Section: The Soluble Mps3nsupporting
confidence: 55%
“…5B). SMC5/6 is known to be recruited to DSBs by Rtt107 when phosphorylated by the DNA damage checkpoint kinase Mec1 (De Piccoli et al 2006;Ohouo et al 2010;Leung et al 2011;Ullal et al 2011). Consistently, the rtt107Δ strain also compromised relocation of DSBs to the NE in both stages of the cell cycle (Fig.…”
Section: The Soluble Mps3nsupporting
confidence: 55%
“…A component of this function for Brc1 is engagement of the error-prone branch of PRR. In keeping with this model, studies of the Brc1 homolog in budding yeast, Rtt107, have shown it to play a role in replication re-start mediated through its interaction with Slx4 (Ohouo et al, 2010;Roberts et al, 2006). However, Slx4 is a considerably larger protein in S. cerevisiae than in S. pombe, and the region required for the Slx4-Rtt107 interaction is absent in fission yeast (Coulon et al, 2004).…”
Section: Brc1-dependent Genome Stability In S Phase 2761mentioning
confidence: 95%
“…This arrangement of domains is conserved in orthologous proteins throughout ascomycete fungi, including Rtt107 protein in Saccharomyces cerevisiae, which is also involved in the cellular responses to replication stress. [30][31][32] The presence of 6-BRCT domains connected by linkers is also found in the PTIP/Swift family of proteins in metazoans, which also appear to function in DNA damage responses. [33][34][35][36] As seen for Brc1, both Rtt107 and PTIP bind γH2A(X) through their C-terminal BRCT domains.…”
Section: Functional Analyses Of the N-terminal Brct Domains Of Brc1 Imentioning
confidence: 99%